1979
DOI: 10.2466/pms.1979.49.2.591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Awareness on an Indicator of Cognitive Load

Abstract: Prior research has shown that the rate of eye blinking is inversely related to cognitive load. In the present study, as in the prior work, some subjects were never told that their eyeblinks were being monitored. However, other subjects were deliberately informed. Each group of subjects performed both easy and difficult arithmetic. Awareness of being monitored reduced the blinking rate. However, the rate was still inversely related to difficulty of the task, even for the informed subjects. The methodological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 2 publications
0
18
1
Order By: Relevance
“…As in the case of fixation duration, these measures provide online measures of instantaneous load. In particular, there seems to be an inverse relationship between cognitive load and blink rate with blink rate decreasing as the cognitive workload increases (Bagley & Manelis, 1979, Brookings, Wilson, & Swain, 1996Chen, Epps, Ruiz, & Chen, 2011). Blink latency has also been found to increase with higher cognitive load (Chen et al, 2011).…”
Section: Eye Movementsmentioning
confidence: 91%
“…As in the case of fixation duration, these measures provide online measures of instantaneous load. In particular, there seems to be an inverse relationship between cognitive load and blink rate with blink rate decreasing as the cognitive workload increases (Bagley & Manelis, 1979, Brookings, Wilson, & Swain, 1996Chen, Epps, Ruiz, & Chen, 2011). Blink latency has also been found to increase with higher cognitive load (Chen et al, 2011).…”
Section: Eye Movementsmentioning
confidence: 91%
“…For example, found that when participants worked hard to neutralize an emotion (e.g., maintaining a neutral expression when viewing a horrific accident scene), their blink rate lowered relative to when they expressed a genuine emotion (e.g., showing fear or horror when viewing the same scene). A decrease in blink rate is a sign of cognitive load (Bageley & Manelis, 1979). In forensic settings, however, such cues are not solely exhibited by liars; truth tellers may have to think hard while answering questions in a cognitively and emotionally complex context.…”
Section: Opportunities In Lie Detectionmentioning
confidence: 99%
“…Liars also need to monitor their own behavior (Vrij & Mann, 2005) and their target's reactions (Burgoon et al, 2008), which places a high demand on the liar's cognitive processing (Carrión et al, 2010). Visible cues to cognitive effort are, for instance, fewer hand and/or arm movements (Ekman, 1997;Memon et al, 2003), less blinking (Bagley & Manelis, 1979), more gaze aversion (Ekman, 1997;Doherty-Sneddon & Phelps, 2005). Attempted behavioral control varies at an individual level and can be influenced by emotional demands and cognitive load.…”
Section: Psychological Processes Underlying Deceptionmentioning
confidence: 99%